The God who comes : Dionysian mysteries reclaimed - Taylor-Perry, Rosemarie (Algora Pub., 2003)
The mystical, ecstatic religions of the Greco-Roman culture, direct threats to the newer Judeo-Christian movements, were obliterated. Here is a thorough description of the Eleusian mysteries, and traces of cultural conflicts at the root of Kosher law and other religious prescriptions that are still with us today.